Influence of maternal plant environment and provenance on alpine bluegrass seed germination - Hermesh, R.; Acharya, S. N. (Canadian Journal of Plant Science, 1992)
Adequate restoration of alpine disturbances requires seed material capable of germinating in high proportions and at a rapid rate. Germination of alpine bluegrass (Poa alpina L.) seeds of different provenances and produced under different environmental conditions was compared under uniform conditions of 16/8 h cycles of light/dark and 22/15 °C temperature. Seeds from nursery plots at the Alberta Environmental Centre, Vegreville, germinated in significantly higher proportions and faster than seeds from the same accessions grown in alpine environments. Alpine bluegrass clones grown in controlled environment chambers set at 22/15 °C and 15/8 °C light/dark with a 16-h photoperiod produced seeds with higher rates of germination and greater cumulative germination than seeds produced in an 8/1 °C regime. It is suggested that alpine blue-grass seeds with high germination percentage and rates are best produced under prairie nursery conditions.Key words: Alpine bluegrass, Poa alpina L., seed germination, maternal environment